Strategic Leadership Paradigms in Organizational Change Management for Sustainability - Suwanphahu, Bunrome (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
The globalization era is complex and uncertain. Organizational leaders play a crucial role in driving the success of the organization. Ultimately, leaders with strategic leadership qualities are able to effectively guide their organizations towards achieving their goals. This article aims to analyze the strategic leadership paradigms in organizational change management for sustainability. A review of various documents provides a conceptual framework for this action. Findings regarding the strategic leadership paradigms, including setting direction and developing organizational strategies, linking operational strategies, innovative creativity, and supporting factors for change, communication, the use of technology and teamwork, and building a sustainable organizational culture, are key paradigms impacting organizational change management to achieve sustainability goals.